Datafied corporate metropolis: initial notes on fintech ecosystems in São Paulo’s informational center - Alves, Caio Zarino Jorge; Silva, Adriana Maria Bernardes da (Geografares, 2026)
This paper situates the problem of sociospatial restructuring stemming from the emergence of fintech ecosystems within São Paulo’s Informational Center. Methodologically, it combines a critical literature review on finance platformization within advanced producer services complexes with the compilation and preliminary systematization of secondary data from the Central Bank of Brazil and Distrito Report 2024. Grounded in an analytical approach that highlights the spatial selectivity of modernization processes in the periphery/semi-periphery of the world-economy, we conceptualize fintech ecosystems in the São Paulo metropolis as functionalizations of contemporary datafication. Accordingly, it advances a research agenda addressing new morphologies, specializations, and hierarchies shaped by interdependencies between startups, Big Tech firms, incumbent banks, investors, and state entities within the current phase of the metropolitan corporate complex.
Keywords: financial geography; fintech ecosystems; São Paulo